Four arms robotic-assisted pulmonary resection—right lower/middle lobectomy: how to do it - Pardolesi, Alessandro; Bertolaccini, Luca; Brandolini, Jury; Gallina, Filippo Tommaso; Novellis, Pierluigi; Veronesi, Giulia; Solli, Piergiorgio (Journal of Thoracic Disease, 2017)
In the last few years, robotic approach for anatomic lung resection has brought an innovative development in minimally invasive thoracic surgery. This study analyzes the technical aspects of performing the hilar dissection for a lobectomy via robotic approach. With a detailed step-by-step description and essential tips and videos, in this paper, we report the procedure to carry out a four-arm robotic middle and lower lobectomy.